PENDAMPINGAN TERHADAP ANAK PANTI ASUHAN YAYASAN DELPITA DENGAN TEMA “ANAK PANTI ASUHAN BERHAK HIDUP SUKSES” - Sinaga, Rini Viri Insy; Lubis, Porkas Sojuangon; Wardani, Widia; Lubis, Muhammad Rum; Mauliza, Sri; Lubis, Muhammad Azmi I. (LPPM Universitas Bina Bangsa, 2025)
Every child has the same right to achieve success, including children living in orphanages. However, the challenges they face are often more complex than children raised in families. This community service was carried out at the Talenta Delpita Orphanage located on Jalan Unika Ujung Gang Sepadan I LK XX, Kwala Bekala Village, Medan Johor District, Medan City. The community service method uses the social intervention method. The social intervention method is one of the methods used in implementing Community Service activities. Social intervention can be interpreted as a way or strategy to help individuals or groups or families or communities in the context of their social lives with the aim of welfare for the community. The results of community service show that orphanage children cannot be justified as children who do not have any motivation to succeed. Orphanage children also cannot be justified as children with a bleak future. Orphanage children also cannot be justified as weak children and cannot do anything. In reality, they are children who can do more, have more potential and are able to fight for the right to success that exists in them, as long as they are willing and able to develop the potential for success that exists, by maximizing the motivation from within and outside that exists in them. This community service concludes that with the right support, children at the Talenta Delpita orphanage have the same potential to achieve success as other children.